2008
DOI: 10.1016/j.virol.2008.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional hierarchy of two L domains in porcine endogenous retrovirus (PERV) that influence release and infectivity

Abstract: The porcine endogenous retrovirus (PERV) Gag protein contains two late (L) domain motifs, PPPY and P(F/S)AP. Using viral release assays we demonstrate that PPPY is the dominant L domain involved in PERV release. PFAP represents a novel retroviral L domain variant and is defined by abnormal viral assembly phenotypes visualized by electron microscopy and attenuation of early PERV release as measured by viral genomes. PSAP is functionally dominant over PFAP in early PERV release. PSAP virions are 3.5-fold more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…The results of the spreading assay correlate to those for the release of MMuLV, shown above, and emphasize the importance of the Gag PPPY motif, but not the PSAP or YPAL motif, in the replication of MMuLV. Likewise, the PPPY motif was recently identified as the dominant L domain in the release of porcine endogenous retrovirus in a functional hierarchy of L-domain activity (19). Yet our results contrast in part with those of a previous report (27) demonstrating a three-to fivefold reduction in VLP levels of MuMLV Gag-YFP harboring the L1 and/or L2 mutations, which suggested a role for PSAP and YPAL motifs in MMuLV budding.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the spreading assay correlate to those for the release of MMuLV, shown above, and emphasize the importance of the Gag PPPY motif, but not the PSAP or YPAL motif, in the replication of MMuLV. Likewise, the PPPY motif was recently identified as the dominant L domain in the release of porcine endogenous retrovirus in a functional hierarchy of L-domain activity (19). Yet our results contrast in part with those of a previous report (27) demonstrating a three-to fivefold reduction in VLP levels of MuMLV Gag-YFP harboring the L1 and/or L2 mutations, which suggested a role for PSAP and YPAL motifs in MMuLV budding.…”
contrasting
confidence: 99%
“…Examples of these dual domains include the PTAP and YPDL motifs in HIV Gag (9,28) and the PSAP and PPPY motifs in Mason-Pfizer monkey virus Gag (11) and porcine endogenous retrovirus Gag (19). Recently, it has been proposed that MMuLV Gag is unique in that it possesses three L domains (27): PPPY (nested in the p12 domain), first identified by Yuan et al (35); PSAP (in the MA domain); and YPAL (at the border between the MA and p12 domains).…”
mentioning
confidence: 99%
“…Studies implicating different types of viruses have demonstrated that defects in virus release in vitro give rise to in vivo attenuation (18,30,32,53). For a rapidly lytic virus such as EMCV, it seems likely that impaired release would decrease propagation and hence contribute to its attenuated phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Virus production was analyzed using an assay for RT activity, which measures virus particles containing RT, or by titration, measuring infectious viruses (297,298,313). Virus production and morphology were studied by transmission electron microscopy (89,192,300) (Fig. 2) or by scanning electron microscopy (154,299) (Fig.…”
Section: Pervsmentioning
confidence: 99%